Chemical Structure of Mangrove Species Rhizophora stylosa as Natural Dyes - Paryanto, Paryanto; Pranolo, Sunu Herwi; Susanti, Ari Diana; Dewi, Kristina Ratna; Rossari, Meydiana (Universitas Diponegoro, 2020)
Textile dyes are divided into two types, natural dyes and synthetic dyes. Natural dyes commonly made from extraction. Extraction is a process in which one or more components are separated selectively from a liquid or solid mixture, the feed, by means of a liquid immiscible solvent. Extraction can be classified into two group, liquid extraction and solid-liquid extraction. Solvents that are usually used in the extraction of natural dyes are aquades and ethanol. The purpose of this research was to determine the chemical structure, especially tannin in natural dyes from mangrove species Rhizophora stylosa through several samples testing natural dyes. Rhizophora stylosa that have been extracted and evaporated will conducted several tests to obtain chemical structures in natural dyes and yield of tannin in natural dyes. Tests carried out include testing FT-IR, and HPLC. Based on FT-IR analysis, the extraction of Rhizophora stylosa containing tannin indicated by the presence of hydroxyl (O-H) in the area of 3385.36 cm-1, aromatic (C-H) in the area of 1365.53 cm-1, carbonyl (C=O) in the area 1646.36 cm-1, esters (C-O) in the area 1217.30 cm-1. While tannin content obtained from the analysis of HPLC were 6.087 ppm.Â